2009
DOI: 10.1007/s00726-009-0330-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Red Bull energy drink on cardiovascular and renal function

Abstract: Energy drink consumption has been anecdotally linked to the development of adverse cardiovascular effects in consumers, although clinical trials to support this link are lacking. The effects of Red Bull energy drink on cardiovascular and neurologic functions were examined in college-aged students enrolled at Winona State University. In a double-blind experiment where normal calorie and low calorie Red Bull were compared to normal and low calorie placebos, no changes in overall cardiovascular function nor blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 27 publications
4
63
1
1
Order By: Relevance
“…Differential acute cardiovascular responses across the various studies could also result from differences in the volume of the ED ingested, thereby reflecting differences in the water load, as well as in the amount of active ingredients consumed (Table 2). Indeed, the 30% lesser volume of the EDs used in the study by Ragsdale et al (31) and Hajsadeghi et al (38) than that used in our study (250 compared with 355 mL) could have contributed to the lack of a significant increase in blood pressure measured over 120 min. Furthermore, although in the study by Worthley et al (32) 250 mL of a sugar-free ED was found to elevate mean blood pressure at 60 min postconsumption, the increase in mean blood pressure (;3.5 mm Hg) was less than that observed at the same time point in our study with 355 mL of Red Bull (;5 mm Hg at 60 min postconsumption) (17).…”
Section: Eds and Hemodynamics: Discrepancies Between Studiesmentioning
confidence: 53%
See 2 more Smart Citations
“…Differential acute cardiovascular responses across the various studies could also result from differences in the volume of the ED ingested, thereby reflecting differences in the water load, as well as in the amount of active ingredients consumed (Table 2). Indeed, the 30% lesser volume of the EDs used in the study by Ragsdale et al (31) and Hajsadeghi et al (38) than that used in our study (250 compared with 355 mL) could have contributed to the lack of a significant increase in blood pressure measured over 120 min. Furthermore, although in the study by Worthley et al (32) 250 mL of a sugar-free ED was found to elevate mean blood pressure at 60 min postconsumption, the increase in mean blood pressure (;3.5 mm Hg) was less than that observed at the same time point in our study with 355 mL of Red Bull (;5 mm Hg at 60 min postconsumption) (17).…”
Section: Eds and Hemodynamics: Discrepancies Between Studiesmentioning
confidence: 53%
“…Similarly, by using a mercury sphygmomanometer to assess blood pressure variables, Hajsadeghi et al (38) investigated the cardiovascular impact of 250 mL of an ED in young healthy subjects and showed no significant changes in blood pressure at 30 min and at 120 min postconsumption. In light of our findings that both systolic and diastolic blood pressures peak at 80-100 min postconsumption, one cannot disregard the possibility that an increase in blood pressure at 60 min postconsumption of the ED in the study by Ragsdale et al (31) and at 120 min postconsumption in the study by Hajsadeghi et al (38) may have been detected as a significant increase if blood pressure had been measured continuously over the 120-min test period.…”
Section: Eds and Hemodynamics: Discrepancies Between Studiesmentioning
confidence: 72%
See 1 more Smart Citation
“…(22) Acute caffeine intake decreases insulin sensitivity, (23) which could explain the rise in blood glucose levels after energy drink consumption documented in some studies. (24) Beaudoin et al demonstrated that caffeine intake reduces insulin sensitivity in a dose dependent manner, with 5.8% increase in insulin for each mg/kg increase in caffeine. (25) A case has been reported of a woman that presented with jaundice, abdominal pain and highly elevated liver enzymes following energy drink overconsumption.…”
Section: Cardiovascular Effectmentioning
confidence: 99%
“…Sobre la actividad cardiovascular, en una prueba de estrés por agua caliente, aminora los cambios en la presión sanguínea e incrementa la tolerancia al dolor (Ragsdale, Gronli, Batool, Haight, Mehaffey, McMahon, Nalli, Mannello, Sell, McCann, Kastello, Hooks y Wilson, 2010).…”
Section: En Humanosunclassified